Silibinin pharmacology and opportunities for therapy in horses - Hackett, Eileen Sullivan, author; Gustafson, Daniel L., advisor; Amberg, Gregory C., committee member; Mama, Khursheed R., committee member; Twedt, David C., committee member (Colorado State University. Libraries, 2011)
Milk thistle extracts have been used as a 'liver tonic' for centuries. In recent years, silibinin, the active ingredient in milk thistle extracts, has been studied both in vitro and in vivo to evaluate the beneficial effects in hepatic disease. It is evident from this research that silibinin significantly increases antioxidant levels and improves outcomes in diseases resulting from oxidant injury. Pharmacokinetic and pharmacodynamics evaluation of silibinin in healthy horses is a precursor to evaluation as a treatment for acute hepatic diseases in the horse. Further, liver disease is poorly characterized in horses living in the United States. Therefore, investigation of hepatic disease in horses was also necessary to evaluate the potential utility of silibinin treatment in disease. It was hypothesized that silibinin consumed orally twice daily in escalating doses over several weeks by healthy horses would have predictable serum levels, low toxicity, and result in a significant increase in antioxidant reserve. Oral silibinin demonstrated poor bioavailability, a short elimination half-life, and did not accumulate when administered twice daily over 7 days. Nonlinear pharmacokinetic behavior was observed with escalating doses, possibly due to saturable enzymatic elimination. As observed in other species, silibinin administration was considered safe and non-toxic in horses. Increase in antioxidant reserve was an important treatment effect of silibinin identified in healthy horses. Hepatic disease in horses in the western United States had a high mortality, and fibrotic and inflammatory conditions were often encountered. Silibinin is indicated in a variety of acute and chronic diseases affecting liver function in horses, as common histologic lesions identified in horses with hepatic disease could be targeted by the multiple known treatment effects of silibinin. Future study is justified to evaluate dose, kinetics, and treatment effects in horses with hepatic disease.
Keywords: equine; silymarin; milk thistle; hepatic